Bivariate Chlodowsky-Stancu Variant of (p, q)-Bernstein-Schurer Operators. (24th April 2019) - Vedi-Dilek, Tuba; Gemikonakli, Eser
Abstract : In this study, it is proposed to define bivariate Chlodowsky variant of( p, q ) -Bernstein-Stancu-Schurer operators. Therefore, Korovkin-type approximation theorems and the error of approximation by using full modulus of continuity are presented. Beside this, we introduce a generalization of the bivariate Chlodowsky variant of( p, q ) -Bernstein-Stancu-Schurer operators and investigate its approximation in more general weighted space. Moreover, the numerical results are discussed in order to validate the accuracy of the bivariate Chlodowsky variant of( p, q ) -Bernstein-Schurer operators.